Temperature Changes of Pulp Chamber during In Vitro Laser Welding of Orthodontic Attachments - Eren İşman; Rıdvan Okşayan; Oral Sökücü; Serdar Üşümez (The Scientific World Journal)
The use of lasers has been suggested for orthodontists to fabricate or repair orthodontic appliances by welding metals directly in the mouth. This work aimed to evaluate the temperature changes in the pulp chamber during welding of an orthodontic wire to an orthodontic molar band using Nd : YAG laser in vitro. A freshly extracted human third molar with eliminated pulpal tissues was used. J-type thermocouple wire was positioned in the pulp chamber. A conductor gel was used in the transferring of outside temperature changes to the thermocouple wire. An orthodontic band was applied to the molar tooth and bonded using light cured orthodontic cement. Twenty five mm length of 0.6 mm diameter orthodontic stainless steel wires was welded to the orthodontic band using Nd : YAG laser operated at 9.4 watt. Temperature variation was determined as the change from baseline temperature to the highest temperature was recorded during welding. The recorded temperature changes were between 1.8 and 6.8°C (mean: 3.3 ± 1.1°C). The reported critical 5.5°C level was exceeded in only one sample. The results of this study suggest that intraoral use of lasers holds great potential for the future of orthodontics and does not present a thermal risk. Further studies with larger samples and structural analysis are required.